Implementation of Fiscal Decentralization in the Digital Era: Effectiveness and Challenges in Indonesia - Putra, I Made Arie Widyasthana Wartana; Suharnoko, Dwi; Salsabila, Faradian; Putri, Dina Dwi Utami (Kolaborasi : Jurnal Administrasi Publik, 2024)
Fiscal decentralization in the digital era brings new opportunities and challenges for its effectiveness in Indonesia. This article aims to analyze the implementation of fiscal decentralization in the digital context, evaluate its effectiveness, and identify the challenges faced. The methodology used includes a literature review and secondary data analysis. The research findings indicate that implementing fiscal decentralization in the digital era can enhance effectiveness in several aspects, such as financial transparency and accountability, efficiency in regional financial management, and increased public participation. However, this implementation also faces several challenges, including disparities in digital infrastructure between regions, limited human resource capacity in the areas, and insufficient regulations supporting the implementation of fiscal decentralization in the digital era. Therefore, although budgetary decentralization in the digital era holds significant potential to improve the effectiveness of regional financial management, serious efforts are needed to address these challenges. This includes investment in digital infrastructure, enhancement of human resource capacity, and the development of regulations that support the practical and safe application of technology.